Stuck in neutral : business and the politics of human capital investment policy - Martin, Cathie J. (Princeton studies in American politics., 2000)
According to conventional wisdom, big business wields enormous influence over America's political agenda and is responsible for the relatively limited scale of the country's social policies. In Stuck in Neutral, however, Cathie Jo Martin challenges that view, arguing that big business has limited involvement in social policy and in many instances desires broader social interventions.Combining hundreds of in-depth interviews with careful quantitative analysis, Martin shows that there is strong support among managers for government-sponsored training, health, work, and family initiatives to enhance workers' skills and productivity. This support does not translate into political action, surprisingly, because big firms are not organized to intervene effectively. Every large company has its own staff to deal with government affairs, but overarching organizations for the most part lobby ineffectively for the collective interests of big business in the social realm. By contrast, small firms, which cannot afford to lobby the government directly, rely on representative associations to speak for them. The unified voice of small business comes through much more clearly in policy circles than the diverse messages presented by individual corporations, ensuring that the small-business agenda of limited social policy prevails. A vivid portrayal of the interplay between business and politics, Stuck in Neutral offers a fresh take on some of the most controversial issues of our day. It is a must read for anyone interested in the past, present, and future of the American welfare state and political economy.